PENGARUH KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR KECAMATAN SAMARINDA KOTA - Mariyana mariyana (ADMINISTRASI PUBLIK, 2019)
The results of the study show that there is no significant relationship between leadership and employee work discipline at the Samarinda City District Office.From the results of calculations that Leadership that occurs in the environment at the Samarinda City District Office has not been able to foster awareness of employees below it in the discipline of work. This is due to the fact that there is still a thought of most employees that the discipline carried out by the leaders cannot be imitated, in the sense that the discipline is carried out only because there is an interest in fearing the leadership above it.The low work discipline of most employees causes a lot of work to be delayed and decreases public confidence in the services provided.The leadership expected by everyone in the Samarinda Kota District Office is transactional and national leadership, which is to expect leaders who have strong, authoritative, consistent and willing to understand the needs of subordinates. As stated by L.M. Berry, (2008: 130) that developing the concept of transformational and transactional leadership is based on Maslow's opinion on the hierarchy of human needs. This connection can be understood by the idea that lower employee needs, such as physiological needs and security can only be fulfilled through the practice of transactional leadership styles. Conversely, P. Bycio et al (2005: 112) suggest that higher needs, such as self-esteem and self-actualization, can only be fulfilled through the practice of transformational leadership styles. In contrast, authoritarian leadership is generally less favored by subordinates, although authoritarian leadership is sometimes needed to support the achievement of a particular target of work. This is illustrated by the opinions of respondents who position authoritarian leadership in the third position of the two previous types of leadership (transaction and transformational).Because the attitude and behavior of the leader becomes the size of the employee in carrying out their duties, discipline cannot grow on its own without motivation coming from outside. Even if awareness of discipline comes from within him, of course there are certain motives that make it such, for example the desire to achieve a certain achievement.